2010
DOI: 10.1007/s10796-010-9232-6
|View full text |Cite
|
Sign up to set email alerts
|

Information systems resources and information security

Abstract: Recent studies suggest that the number of information security incidents has increased dramatically and has caused significant economic loss worldwide. Awareness of the significance of information security is evidenced by a rapid increase in information security investments. Despite the fact that information security has taken on a new level of importance, academic research on this subject is still in its infancy. A review of literature indicated that past studies largely took a resource based view, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…That is, they outline strategies, plans, and investments based on an understanding of business objectives, values, and needs. Previous research have shown that organizations with business competent information security executives conduct proper management of information assets and effective allocation of resources (Chang and Wang, 2010). In line with the findings from the exploratory study, we believe that a deep understanding of the business environments, processes and the organizational goals should enable the development of effective information security strategies, provide information security services that fit organizational needs, and enable a more effective coordination of information security activities.…”
Section: The Role Of Business-based Information Security Managementsupporting
confidence: 83%
See 3 more Smart Citations
“…That is, they outline strategies, plans, and investments based on an understanding of business objectives, values, and needs. Previous research have shown that organizations with business competent information security executives conduct proper management of information assets and effective allocation of resources (Chang and Wang, 2010). In line with the findings from the exploratory study, we believe that a deep understanding of the business environments, processes and the organizational goals should enable the development of effective information security strategies, provide information security services that fit organizational needs, and enable a more effective coordination of information security activities.…”
Section: The Role Of Business-based Information Security Managementsupporting
confidence: 83%
“…While all the aforementioned approaches have increased the understating of problems related to behavioral information security governance, and potential solutions to those problems, none of them have developed and empirically tested a theoretical model that include behavioral information security governance constructs. In fact, by reviewing related work the authors of the present paper only found four studies that fulfil this criteria (Straub, 1990;Kankanhalli, 2003;Knapp et al, 2007;Chang and Wang, 2010). Considering the lack of empirical studies related to behavioral information security governance, the present study aims at complementing the body of literature on behavioral information security governance by exploring, developing, and empirically testing a theoretical model explaining the establishment of security knowledge sharing throughout an organization.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Apart from studies done by Xu and Bowrin (2005), Thorpe (2005) and Duncan and Duggan (2008) information security remains a relatively under-researched field in the Caribbean context. This study aims to add to the reservoir of local knowledge and in this endeavour we will use the information security model developed by Chang and Wang (2010). Peltier (2005) states that information security "encompasses the use of physical and logical data access controls to ensure the proper use of data and to prohibit unauthorized or accidental modification, destruction, disclosure, or loss of access".…”
Section: Caribbean Contextmentioning
confidence: 99%